Tobacco Smoking During Pregnancy Is Associated With Increased Risk of Moderate/Severe Bronchopulmonary Dysplasia: A Systematic Review and Meta-Analysis - González-Luis, Gema E.; van Westering-Kroon, Elke; Villamor-Martinez, Eduardo; Huizing, Maurice J.; Kilani, Mohammed A.; Kramer, Boris W.; Villamor, Eduardo (Frontiers in Pediatrics, 2020)
Epidemiological evidence and animal studies support that intrauterine exposure to tobacco smoke disturbs lung development and have a negative effect in the pulmonary health of the offspring. Recent population-based studies have linked exposure to maternal smoking during pregnancy to increased risk of bronchopulmonary dysplasia (BPD). However, this association has not yet been systematically investigated. We aimed to conduct a systematic review of studies reporting on tobacco smoking during pregnancy as potential risk factor for BPD. PubMed/MEDLINE and EMBASE databases were searched. Studies were included if they examined preterm infants and reported primary data that could be used to measure the association between fetal exposure to maternal tobacco smoking and the presence of BPD. BPD was defined as supplemental oxygen requirement on postnatal day 28 (BPD28; all BPD), at the postmenstrual age (PMA) of 36 weeks (BPD36; moderate/severe BPD), or as need for ⩾ 30% oxygen and/or positive pressure at 36 weeks PMA (severe BPD). A random-effects model was used to calculate risk ratios (RR) and 95% confidence intervals (CI). Of 2894 potentially relevant studies, 33 met the inclusion criteria. The included studies evaluated 171,772 infants and included 30,445 cases of exposure to maternal smoking and 25,340 cases of BPD of any severity. Meta-analysis showed a significant association between tobacco smoking during pregnancy and BPD36 (17 studies, RR 1.126, 95% CI 1.008 to 1.259, p=0.036), but could not demonstrate a significant association between tobacco smoking during pregnancy and BPD28 (16 studies, RR 1.021, 95% CI 0.924 to 1.129, p=0.681), or severe BPD (3 studies, RR 1.143, 95% CI 0.528 to 2.478, p=0.734). In conclusion, our data suggest that tobacco smoking during pregnancy increases the risk of moderate/severe BPD. Our results highlight the detrimental effects of tobacco smoking and reinforce the hypothesis of the involvement of prenatal insults in the etiopathogenesis of BPD.